Associations of cardiovascular health and social determinants of health with the risks of all-cause and cause-specific mortality - Boxuan Pu; Zun Wang (PLoS ONE, 2025)
Background While cardiovascular health (CVH) and social determinants of health (SDoH) are independently associated with mortality, their combined effects on mortality remain unclear. The study aimed to examine the mediating, interacting, and combined effects of CVH and SDoH on mortality risks. Methods We analyzed data from 20,096 adults in the National Health and Nutrition Examination Survey 2007–2018. CVH was assessed using the Life’s Essential 8 (LE8) score and categorized into low, moderate, or high. Cumulative unfavorable SDoH burden was assessed and divided into low and high burdens of unfavorable SDoH. Multivariate Cox regression models were used to analyze the combined associations of SDoH and CVH with mortality. Mediation analysis was used to analyze the mediating role of CVH between SDoH and mortality. Interaction effects were tested by adding interaction terms between CVH and SDoH in the Cox models. Results A high burden of unfavorable SDoH was associated with higher risks of all-cause, cardiovascular disease (CVD), and cancer mortality. CVH significantly mediated these associations, accounting for 16.70% for all-cause mortality, 22.22% for CVD mortality, and 17.70% for cancer mortality. A significant additive interaction between SDoH and CVH was observed for all-cause mortality. Compared with individuals exhibiting neither risk factor, those with both low CVH and a high burden of unfavorable SDoH had significantly elevated risks of all-cause (hazard ratio [HR]: 4.60; 95% confidence interval [95% CI]: 2.87–7.37), CVD (2.80; 1.10–7.10), and cancer mortality (6.10; 2.13–17.50). Conclusions The coexistence of low CVH and a high burden of unfavorable SDoH was associated with increased risks of all-cause, CVD, and cancer mortality. These findings have implications for integrating SDoH and CVH in clinical practice and public health strategies to improve survival.